Dynamic Response of a Rotating Assembly under the Coupled Effects of Misalignment and Imbalance. (19th October 2020) - Desouki, Mohamed; Sassi, Sadok; Renno, Jamil; Gowid, Samer Abdelazim
Abstract : In rotating machinery, the second most common fault after imbalance is misalignment. Misalignment can have a severe impact on equipment and may reduce the machine's lifetime considerably. In this paper, the simultaneous effect of imbalance and misalignment (parallel or angular) on the vibration spectra of rotating machinery will be discussed. A numerical model is developed and used to obtain the time and frequency responses of the rotor-coupling-bearing system to the simultaneous effect of these faults. The numerical model shows that the imbalance was mainly related to the peak located around 1X, whereas misalignment was linked to the peak around 2X. In addition, the parallel misalignment fault magnifies the 2X amplitude of the displacement response, whereas the response of angular misalignment is captured at the 2X and 4X amplitudes. This study also examines the effects of changing the model's rotational speed, misalignment level, and coupling type for angular and parallel misalignments.